Ovarian cancer: origin and factors involved in carcinogenesis with potential use in diagnosis, treatment and prognosis of the disease - Zavesky, L; Jancarkova, N; Kohoutova, M (Neoplasma, 2011)
Ovarian cancer representing the most lethal gynecologic malignancy escapes from the efforts to manage the disease. We reviewed the current state of the research considering three main concepts on origin of ovarian cancer including epithelial-mesenchymal transition, secondary origin from Müllerian system and cancer stem cell hypothesis. Cytogenetic and molecular characteristics of ovarian cancer are focused particularly on microRNA expression studies revealing huge potential in recent years, although other transcriptomic, proteomic, epigenetic, epidemiologic and immunological factors are touched upon, too. Routine and investigated diagnostic and treatment methods are outlined and several factors revealed to be associated with prognosis of the disease. Despite the huge progress on elucidating factors involved in ovarian cancer carcinogenesis, still remains urgent need to improve both the diagnostics as well as the treatment.
Keywords: Cell Transformation, Neoplastic; Female; nádory vaječníků; Ovarian Neoplasms; Humans; ženské pohlaví; prognóza; lidé; Prognosis; nádorová transformace buněk